0234 Salivary α-Amylase Response to Repeated Exposure to Acute Stressors Is Altered by Sleep Deprivation. (25th May 2022) - Lundholm, Kirsie; James, Stephen; Honn, Kimberly; Hansen, Devon; Van Dongen, Hans; Satterfield, Brieann
Abstract: Introduction: Salivary α-amylase (sAA), a biomarker of autonomic nervous system (ANS) activity, is believed to reflect physiological responsiveness to stressors. Although exposure to stressors often co-occurs with sleep deprivation, little is known about their combined effects. We investigated the sAA response following repeated exposure to acute stressors at well-rested baseline and during total sleep deprivation (TSD). Methods: As part of a larger study, N=8 healthy subjects (ages 29.0±6.6; 4 females) participated in a 4-day/3-night laboratory-based experiment. Subjects had 38h TSD preceded and followed by 10h sleep opportunities (22:00–08:00). On days 2 (baseline) and 3 (TSD), subjects completed two (A, B) deadly-force decision-making simulations in a high-fidelity shooting simulator with 30min rest between sessions. During each simulation, subjects (who were civilians) acted as police officers while viewing interactive videos depicting stressful law enforcement emergency response scenarios involving deadly-force decision-making. In these scenarios, subjects attempted to de-escalate the situations in the scenarios using verbal commands. If unsuccessful, they were to determine if the use of (simulated) deadly force was necessary and respond accordingly. Saliva samples were collected immediately before the first simulation of the baseline and TSD days, and immediately, 15min, and 30min after each simulation. Samples were assayed in duplicate using a sAA kinetic enzyme assay; results were normalized against the first pre-stressor sample of the baseline day. Results: Post-simulation sAA values normalized to reference were analyzed with mixed-effects ANOVA with fixed effects of day and sample and their interaction and a random effect over subjects on the intercept. There was a significant effect of sample (F[5, 76]=3.38, p=0.008) indicating that sAA spiked immediately after each deadly-force decision-making simulation. Planned comparisons revealed significantly blunted sAA during TSD compared to baseline immediately after the second simulation of the day (t[76]=2.09, p=0.040). Conclusion: In our sample of civilian subjects, the deadly-force decision-making simulations elicited a sAA response, which was blunted after the second simulation on the day subjects were sleep-deprived, suggesting that TSD mediates the biological response to repeated exposure to acute stressors. Whether this result generalizes to police officers and military personnel trained in deadly-force decision-making remains to be determined. Support (If Any): ONR grant N00014-13-1-0302